Meningkatkan Keterampilan Regulasi Diri Anak di Era Digital Melalui Pembelajaran Kisah Dabbhapuppha Jataka - Merlin, Eka (Hasta Wiyata, 2024)
In the digital age, children face great challenges in developing self-regulation skills, which are essential to help them manage their emotions, control impulses, and make wise decisions. Technology that offers instant gratification and pleasure is often an obstacle to the development of patience and self-control. However, on the other hand, the digital era also offers solutions through the delivery of moral stories more effectively and attractively using digital media. One approach that can be used to overcome this challenge is through learning moral stories such as Jataka, which is rich in educational values. The story of Dabbhapuppha Jataka highlights the importance of self-control and wisdom in facing challenges and changes in life. This research aims to identify the moral values in the story of Dabbhapuppha Jataka which can be developed as learning materials to improve self-regulation skills in children in the digital era. The research method used is library research, where various relevant literature is studied to explore the moral values contained in the story. In addition, digital media is also recognized as a potential means to convey the moral message of this story in a more interesting and easy-to-understand way for children. The results of this study show that the moral values of the Dabbhapuppha Jataka story can help children in developing self-regulation, including the ability to control emotions and actions in facing various life challenges in the digital era.